2017
DOI: 10.1159/000456545
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Paediatric Patients with Central Precocious Puberty Treated with Intramuscular Triptorelin 11.25 mg 3-Month Prolonged-Release Formulation

Abstract: Background/Aims: A meta-analysis was undertaken to assess the effect of triptorelin 11.25 mg 3-month prolonged-release formulation in central precocious puberty (CPP). Methods: All available clinical studies with triptorelin 11.25 mg were included. The primary outcome was the proportion of children with suppressed luteinising hormone (LH) response (peak LH ≤3 IU/L) to the gonadotrophin-releasing hormone (GnRH) test 3 months after triptorelin 11.25 mg injection. Secondary outcomes included: the proportion with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
(32 reference statements)
2
13
0
3
Order By: Relevance
“…Meta‐analyses may have been missed by our search strategy for this particular analysis (which was not a systematic review). A positive note is that meta‐analyses on puberty are continually being published (e.g., Bertelloni, Massart, Miccoli, & Baroncelli, ; Deng et al., ; Durand, Tauber, Patel, & Dutailly, ; Li et al., ; Ullsperger & Nikolas, ). Given the breadth and quantity of research on puberty, meta‐analyses will continue to be particularly useful for synthesizing the literature on puberty in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses may have been missed by our search strategy for this particular analysis (which was not a systematic review). A positive note is that meta‐analyses on puberty are continually being published (e.g., Bertelloni, Massart, Miccoli, & Baroncelli, ; Deng et al., ; Durand, Tauber, Patel, & Dutailly, ; Li et al., ; Ullsperger & Nikolas, ). Given the breadth and quantity of research on puberty, meta‐analyses will continue to be particularly useful for synthesizing the literature on puberty in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Three-monthly depot preparations, also administered via intramuscular injection, have also been used to treat CPP, particularly in Europe [51]. Several studies as well as a meta-analysis have suggested that the degree of biochemical suppression achieved with 3-monthly dosing is consistently less than that seen with monthly GnRHa administration [51][52][53][54]. However, the clinical response to treatment appears to be similar based on limited data.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Three-monthly depot preparations, also administered via intramuscular injection, have also been used to treat CPP [44]. Several studies have suggested that the degree of biochemical suppression achieved with 3-monthly dosing is consistently less than that seen with monthly GnRHa administration [1, 42,[44][45][46][47]. Nonetheless, the clinical response to treatment appears to be equivalent although minimal comparative information is available.…”
Section: Treatmentmentioning
confidence: 99%